Appendicularian distribution and diversity in the southern Gulf of Mexico Distribución y diversidad de apendicularias en el sur del golfo de México - César Flores-Coto; Laura Sanvicente-Añorve; Marina Sánchez-Ramírez (Revista Mexicana de Biodiversidad, 2010)
The diversity and distribution of appendicularians on the continental shelf and upper part of the oceanic sea in the southern Gulf of Mexico is analyzed here for the first time. Samples were collected in September 2003 using a fine mesh net. Twenty species were identified, of which Fritillaria venusta and Pelagopleura oppressa are first records for the Gulf of Mexico. Oikopleura species occur throughout the area, with greatest abundances in the upwelling waters of the inner shelf off Yucatán and Campeche. The greatest abundances of Fritillaria species and of the other genera were recorded in the mid, outer shelf, and oceanic areas of Campeche and Tabasco that are influenced by continental water discharges and an oceanic gyre. Diversity and abundance varied in differing directions, with high abundance and low diversity characterizing the costal areas and low abundance and high diversity in the mid, outer shelf, and oceanic areas. The distribution of appendicularian species appears to be influenced by upwelling currents, gyres, water column depth, continental water discharges, salinity, and temperature. However, it could be assumed that the reasons behind these physical environmental factors include the food supply, a short life cycle, and high reproductive efficiency, factors that are commonly associated with distribution. Se analiza por primera vez la diversidad y distribución de las apendicularias en la capa superficial de la columna de agua de la plataforma continental del sur del Golfo de México. Las muestra se recolectaron en septiembre de 2003 usando una malla fina- Se identificaron 22 especies de las cuales Fritillaria venusta y Pelagopleura opresa tienen aquí su primer registro para el Golfo de México. Las especies de Oikopleura ocurrieron en toda el área con sus mayores abundancias en aguas de surgencia que corren sobre la plataforma de Yucatán y Campeche. La mayor abundancia de las especies de Fritillaria y de los otros géneros se registro en la plataforma media, externa y área oceánica de Campeche y Tabasco que están influenciadas por las descargas de aguas continentales y un giro oceánico. La diversidad y abundancia varían en sentido contrario una de otra; alta abundancia y baja diversidad caracterizan a las áreas costeras, en tanto baja abundancia y alta diversidad ocurren en la plataforma media, externa y área oceánica. La distribución de las especies parece estar influenciada por las corrientes de la surgencia, giros, profundidad del área, descargas de aguas continentales, salinidad y temperatura. Sin embargo, puede asumirse que detrás de estos factores físicos están la disponibilidad de alimento, el corto ciclo de vida y la alta eficiencia reproductiva, como los factores mas comúnmente asociados a su distribución.